Urgensi Pendidikan Islam dalam Mewujudkan Masyarakat Madani - A. Munawwir ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2019)
The article delineates the objective of Islamic education as a means to establish a Madani society. The general aim of education invariably directs to positive goals, including education with Islamic adjectives as the suffix. What makes the objective of Islamic education and other conventional educations different lies merely in norms and values founding it, namely Islamic values originating from the Quran and Hadith. The article showed that in Islamic education, the end of the ideal personality development as humans is the establishment of a Madani society. The characteristics of the alumnus of Islamic education, among others, are having a healthy state of mind, fast in resolving problems, possessing a strong faith to control oneself, and capable of mastering social sensitivity. The research demonstrated that Islamic education does not only orient towards individual interest but also the establishment of relationships among humans to build a Madani society.